Acoustic energy distribution in space around the pipe outlet - WEYNA, Stefan (Archives of Acoustics, 2007)
Visualization system, by serving a dual role as a provider of exploration and exposition capabilities, have became indispensable to the analysis of computational fluid dynamics (CFD) results. In the acoustical practice, up until the last two decades, the study of vectors acoustic fields and noise flow visualisation are rather seldom. But direct measurement of the flow intensity sound as the energetic fields and graphically description of the results, can explain a diffraction and scattering phenomena occur on the real noise sources and solved in practical way a lot of engineering problems. Based on the research with intensity technique and using selected visualizations methods, in the publication are demonstrate in graphical form the sound intensity effects in the space around outlet region of cylindrical pipe. The duct model have a partly square and barrel shaped cross-section. The outlet research space was scanning with intensity probe measured the x, y and z components of sound intensity vector.Direct measurement of the acoustic power flow around outlet can explain all diffraction and scattering phenomena occur in this region and the noise generated by inside flow and around outlet of duct is an environmental concern in engineering practice.